(untitled) (TAJ: Journal of Teachers Association, 2010)
Road traffic accident is one of the important causes of mortality and morbidity. Pedestrians frequently fall victim of injury and death. Among the causes of accidents are fault of victim, fault of driver, fault of vehicle, wrong signaling, type of vehicle etc. By means of identifying pattern of injuries, Police can ascertain the type of vehicle responsible for accident. DOI: 10.3329/taj.v22i1.5041 TAJ 2009; 22(1): 147-151